Marginal fit changes during porcelain firing cycles - (:unkn) unknown (My University, 1995)
The marginal fit changes that occur during the procelain firing cycles of palladium-copper and nickel-chromium copings both with shoulder and chamfer finish lines were investigated with scanning electron microscopy. Three copings from each alloy test group were used as nonporcelainized controls. Comparisons of the firing cycles revealed a greater change during the degassing stage, and the opaque firing caused a decrease in marginal gap. There was a small increase in gap size after firing body porcelain. The marginal fit change for the palladium-copper copings (19.39 microns) during degassing was significantly greater than that for the nickel-chromium copings (8.65 microns). However, no significant differences were found when the effects of margin design and porcelain proximity to fit of metal-ceramic crowns were compared.
Keywords: Hot Temperature; Microscopy, Electron, Scanning; Chromium Alloys; Copper; Crowns; Dental Abutments; Dental Alloys; Dental Casting Technique; Dental Porcelain; Dental Prosthesis Design; Dental Veneers; Palladium; Probability; Surface Properties